INVESTIGATING ENGLISH DEPARTMENT STUDENT’S ABILITY IN COMPREHENDING ENGLISH READING EXPOSITION TEXT - Irwanto, Richard; Afrianto, Afrianto; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: Reading comprehension is a vital component of the learning process,facilitating the acquisition of essential knowledge and information. This study investigates the proficiency of third-year English language education students in understanding expository reading texts. The research cohort comprises 90 students, and the methodology involves the use of exposition texts, focusing on five key aspects: finding the main idea, locating references, understanding vocabulary, making inferences, and detailing information. A test comprising 50 items serves as the instrument for assessment. Each item encompasses the aforementionedaspects, with 10 questions allocated for each. The findings indicate that third-year English language education students exhibit an average comprehension level of English exposition texts, with an overall percentage score of 65.46. Notably, the aspect of Determining the Main Idea yielded the lowest results, while the Locating Reference aspect garnered the highest scores. These findings provide valuable insights for educators to tailor their teaching approaches and enhance students' reading comprehension skills, particularly in the identification of main ideas. By addressing these areas of improvement, teachers can optimize learning experiences and foster greater proficiency in reading comprehension among students.Keywords: Investigating, Comprehending Ability, Exposition Texts